Analyzing the mechanical behaviour of sisal fiber reinforced IPN matrix. (2021) - Bernard, S. Stephen; Suresh, G.; Srinivasan, T.; Srinivasan, S.; Kaarmugilan, N.; Naveed, L. Mohamed; Kiranmouli, N.; Mahalakshmi, C.S.
Abstract: The studies of composite materials are widely encouraged by various engineering product developers due to its enhanced compatibility and physical properties. This course of study deals with a new combination of sisal fiber reinforcement with IPN (Interpenetrating Polymer Networks) resins. The mechanical behaviour of sisal and IPN resins laminates are observed and studied in this experiment. Various proportions of sisal fiber in corporations were carried out such as 10%, 20%, 30%, 40%, 50%. These laminate structures were experimentally tested under tensile testing, impact testing and flexural testing. The micro structural behaviour of the laminates structures were viewed using scanning electron microscope. The entire results obtained by using experimentation were cross verified using ANSYS software. Finally the results of both experimental and finite element method using ANSYS software were found to be in good co-relation.